Detection of Enterohemorrhagic Escherichia Coli O157 in Sheep and Goats Using Fluorogenic and Chromogenic Culture Media - SAEED, ALI YAHYA; IBRAHIM, KHALID SOBHI (Science Journal of University of Zakho, 2013)
This study was carried out for the first time to investigate the occurrence of E. coli O157 in sheep and goats in Duhok province, Iraq. A total of 320 samples were collected from April to July 2009 as following: 100 fecal samples from sheep, 100 fecal samples from goats, 60 samples from sheep milk and 60 samples from goat milk. E coli O157 was isolated from 3 (3%) sheep fecal samples and 2 (2%) from goat fecal samples, while no E. coli O157 was detected in the milk samples from sheep and goats. E. coli O157 was detected only among E. coli isolates which were sorbitol non fermentative but MUG positive, while no E. coli O157 was detected among E. coli isolates which were negative for both sorbitol and MUG. All E. coli O157 isolates were resistant to 6 among 12 antimicrobial agents used in vitro drug sensitivity test